Pengaruh Gratitude dan Wisdom terhadap Hedonisme pada Mahasiswa Universitas Negeri Semarang - Sofi Azizah; Sigit Hariyadi (Universitas Nahdlatul Ulama Blitar, 2026)
A hedonistic lifestyle is increasingly found among college students. This condition not only changes shopping patterns and outlook on life, but also impacts psychological conditions and character formation. This study aims to determine the effect of gratitude and wisdom on a hedonistic lifestyle in college students. The research design used is quantitative with a correlational approach. This study involved 544 active college students through a cluster sampling technique. Data were collected using a Likert scale consisting of a gratitude scale (α = 0.858), a wisdom scale (α = 0.812), and a hedonism scale (α = 0.867). Data analysis used multiple linear regression after the classical assumption test was met to examine the simultaneous and partial effects of both independent variables on a hedonistic lifestyle. The results of the hypothesis test showed that gratitude and wisdom were negatively related to hedonism in college students where gratitude (β = -0.191), wisdom (β = -0.149), while both variables simultaneously influenced hedonism with a significant value of (R2 = 0.128). These findings confirm that developing gratitude and wisdom can be a preventive strategy for a hedonistic lifestyle, contributing to character education and positive psychology in higher education.